Social Media, Citizenship and New Social Movements: The Role of Facebook Use in the Construction of Collective and Civic Identities by the Indignados Movement in Greece and France - Papa, Venetia (Departmene of Communication and Internet Studies, Faculty of Communication and Media Studies, Cyprus University of Technology, 2015)
At the dawn of the 21st century we witness an upsurge in mobilization and collective action by a wide range of activists and groups engaging in social and political protest, all over the world. What these movements have in common is not only their association with the global financial crisis but also their extensive use of online social media like Facebook and Twitter for mobilization, participation and coordination. Thus, the Indignados movement which sprung in Southern Europe in 2008, constitute a new phenomenon that deserves to be studied in its own right, not only as a form of social movements per se, but also with regard to the role of digital technologies in collective action. Scholars from a wide range of disciplines have tended to focus on questions about the role of the internet in protest, without attending to the changing meaning of what it means to be a citizen within such movements and through their practices and discourses (see Bennett & Segerberg, 2012). Two questions in need of empirical study and which remain unanswered in the literature are: 1. How is civic and collective identity constructed within current constellations of social movements such as the Indignados? 2. How is this construction process mediated by the use of Facebook? This dissertation responds to this need through an empirical study of the discourses and online content of Indignados activists in France and Greece. Drawing an analytical framework from the components of civic and collective identity, it brings together elements that are necessary for a two-level analysis: a) the tangible aspects such as the practices of movements and their participants and b) the ideational aspects such as the feelings of activists within the movement and in relation to the nation. More specifically, this thesis aimed, first, at mapping different forms and processes attached with the construction of civic and collective identity through the discourses of actors. By the use of semi-structured interviews and online content, we attempted to discern and analyse the actors’ belonging, practices, identification and values and principles within the political community in question (the nation-state) and the collectivity (the Indignados), exploring the multiple and complex layers of their feelings. The second objective was to explore the role of Facebook in this process, which allowed us to critically evaluate the potential of social media in the negotiation of civic and collective identity in both meaning and practice. This dissertation provides some insights regarding the figure, shape and nature of citizens in the Indignados movements, arguing for a redefinition of civic identity as a dynamic and unfixed entity based on the everyday struggles and practices of individuals. Along with this, collective ! vii! identity among the Indignados could be qualified as hybrid, multi-layered and open-ended, by pointing out the different elements which coexist within the movement such as politically diverse individuals, different political flows and discourses and new forms of belonging. The role of Facebook seems to be more complex. Several elements found online (e.g. civic talk, creation of collective frames of reference around actions) certainly contribute to the reproduction of civic and collective identities and seem to create a fertile ground for empowerment and the construction of active citizenship in the Indignados movement. However, further research is needed in order to demonstrate the long-term efficacy of such communicative practices in movement outcomes and trajectories.
Keywords: Citizenship; Civic identity; Collective identity; Online social media